Mitochondrial Transport Proteins - Palmieri, Ferdinando (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Mitochondrial transporters are membrane-inserted proteins which provide a link between metabolic reactions occurring within the mitochondrial matrix and outside the organelles by catalyzing the translocation of numerous solutes across the mitochondrial membrane. They include the mitochondrial carrier family members, the proteins involved in pyruvate transport, ABC transporters and channels, and are, therefore, essential for many biological processes and cell homeostasis. Identification and functional studies of many mitochondrial transporters have been performed over the years using both in vitro and in vivo systems. The few recently solved structures of these transporters have paved the way for further investigations. Furthermore, alterations in their function are responsible for several diseases.